Gangguan Kecemasan Pada Tokoh Cath Dalam Novel Fangirl Karya Rainbow Rowell - Fadlah Wulansani; Saprudin (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2022)
This research is entitled Anxiety Disorders in Cath Characters in Rainbow Rowell's Fangirl Novel. In the novel Fangirl tells the story of a woman named Cath, she has an anxiety disorder. He always thinks what he's doing is wrong, he's also not very sociable. Every time he passed the crowd, the anxiety disorder would appear in him. In his early years he began to carry out activities as a student. Usually he will be accompanied anywhere by his twin brother, Wren, but since they entered the world of lectures, Wren doesn't want to live with Cath. So Cath had to go through the world of lectures without Wren. But even though Cath has an anxiety disorder she is good at writing fanfiction. Everything that bothers him will be vented by writing the fanfiction. The purpose of this study was to analyze the form of Cath's anxiety disorder. The method used by researchers in this study is a qualitative descriptive method. The approach that will be used is a literary psychology approach. From the results obtained in this study, Cath has 2 forms of anxiety disorders, the first is Social Anxiety Disorder (SAD) and the second is Generalized Anxiety Disorder (GAD). Social anxiety disorder occurs when Cath feels very resentful of having to interact in terms of performance. If generalized anxiety disorder occurs for no apparent reason, the sufferer will feel worried. Having an anxiety disorder greatly interferes with Cath's ability to carry out any activities, and also annoys those around her. Even his roommates felt uncomfortable seeing Cath who was always alone in his room. Even Cath had refused his friend's invitation to have lunch in the canteen and he preferred to eat alone in his room. However, over time Cath was able to overcome the anxiety disorder with the help of his roommate in the dormitory. The theory that will be used by the author in this study uses the theory of anxiety disorders from Sigmund Freud.